Physico-chemical properties of Dhepa River in Dinajpur District of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
Among different water quality parameters dissolved oxygen, transparency, pH, PO4-P and depth varied significantly among the sampling sites. The pH value in the present investigation remained a buffer condition (6.50- 7.90). Dissolved oxygen was ranges from 3.80 to 11.60 mg/l throughout the study periods. PO4-P concentration was observed highest (0.30 mg/l) in sampling site 2. On the basis of physical, chemical aspects sampling site 3 and sampling site 5 (situated in gosaipur and chandandoho) found in better condition in terms of limnological aspects. However, it could be concluded that Dhepa River will play important role in riverine fisheries and for further fisheries management.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22041 J. Environ. Sci. & Natural Resources, 6(1): 59-67 2013